2017
DOI: 10.1126/sciadv.1601858
|View full text |Cite
|
Sign up to set email alerts
|

Explaining recurring maser flares in the ISM through large-scale entangled quantum mechanical states

Abstract: Simultaneously recurring maser flares from different molecular species in the ISM can be explained with superradiance.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…As a result molecules contained within a gas act as a unit, as opposed to independent entities, and behave cooperatively in a manner that strongly affects the characteristics of the gas and the radiation emanating from it. As was discussed in (see also Rajabi & Houde 2016a,b;Rajabi & Houde 2017), SR will take place when the following conditions are met: i) the population levels of the relevant molecular transition 1 Dicke's superradiance is a quantum mechanical effect that was introduced by R. H. Dicke in a seminal paper more than 60 years ago (Dicke 1954). This phenomenon should not be confused with "black hole superradiance," which has also been considered within the context of the FRB problem (e.g., Rosa & Kephart 2018;Conlon & Herdeiro 2018).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…As a result molecules contained within a gas act as a unit, as opposed to independent entities, and behave cooperatively in a manner that strongly affects the characteristics of the gas and the radiation emanating from it. As was discussed in (see also Rajabi & Houde 2016a,b;Rajabi & Houde 2017), SR will take place when the following conditions are met: i) the population levels of the relevant molecular transition 1 Dicke's superradiance is a quantum mechanical effect that was introduced by R. H. Dicke in a seminal paper more than 60 years ago (Dicke 1954). This phenomenon should not be confused with "black hole superradiance," which has also been considered within the context of the FRB problem (e.g., Rosa & Kephart 2018;Conlon & Herdeiro 2018).…”
Section: Introductionmentioning
confidence: 78%
“…In previous works on SR, whether dealing with star-forming regions (Rajabi & Houde 2017), the surroundings of evolved stars (Rajabi & Houde 2016b) or FRBs , we consistently focused on situations where SR is initiated when the inversion level is high enough to bring the column density nL of the inverted population (n = N/(AL)) above the critical threshold (nL) crit where the time-scale of SR…”
Section: Resultsmentioning
confidence: 99%
“…Hot and dense gas in those shocks can illuminate parts of the disc altering the pumping conditions. Rajabi & Houde (2017) suggested that periodic and seemingly alternating periodic flares in the methanol and water maser lines in G107.298+5.639 can be explained within the context of superradiance theory.…”
Section: Introductionmentioning
confidence: 99%
“…Dicke's superradiance (SR; Dicke 1954) has been the subject of intensive research in the physics community for decades (Gross & Haroche 1982;Benedict et al 1996). However, it had remained unknown to the astronomy community until its recent applications to the interstellar medium (ISM) (Rajabi & Houde 2016a,b;Rajabi 2016;Rajabi & Houde 2017). SR, a coherent radiation mechanism, can provide explanation for strong radiation bursts taking place over a wide domain of time-scales ranging from sub-seconds (Mathews 2017;Houde et al 2019;Houde, Mathews & Rajabi 2018) to several years (Rajabi & Houde 2016b).…”
Section: Introductionmentioning
confidence: 99%